A study on microstructure of porous TiNbZr alloy produced as biomaterialUntersuchung des Gefuges einer porosen TiNbZr-Legierung zur Herstellung von Biowerkstoff - Kaya, M.; Yakuphanoğlu, Fahrettin (Wiley-V C H Verlag Gmbh, 2019)
In the present study, titanium-based biomaterial (Ti-10Nb-10Zr) with different porosity was fabricated by sintering at different temperatures. The porosity of fabricated samples is close to natural bone; also the compression strengths of the samples are higher than that of natural bone. The phases named alpha and beta are seen in the microstructure of samples fabricated, but alpha phase partially converts into beta phase with increasing sintering temperature. Porosity decreases with increasing sintering temperature, and compressive strength increases with decreasing porosity. Elastic modules of fabricated samples are close to natural bone, so these materials don't cause wear of bone.
Untersuchung des Gefüges einer porösen TiNbZr-Legierung zur Herstellung von Biowerkstoff
Keywords: TiNbZr alloy; porous materials; biomaterials; microstructure; sintering